Structure-based screening and molecular dynamics simulation studies for the identification of potential acetylcholinesterase inhibitors - Ganeshpurkar A.; Singh R.; Gore P.G.; Kumar D.; Gutti G.; Kumar A.; Singh S.K. (My University, 2025)
Alzheimer’s disease (AD) is an irreversible, progressive neurodegenerative disease characterised by the appearance of amyloid β plaques and neurofibrillary tangles in the brain. The loss of cholinergic neurons is considered to be one of the contributing factors for cognitive and memory deficits in the disease. Donepezil, the most successful and prescribed drug to treat the symptoms of AD, is acetylcholinesterase (AChE) inhibitor that improves the memory and brain’s cognitive functions. In this study, the pharmacophoric features of donepezil were mapped from its cocrystal with AChE and were used to screen the Zinc15 database. The obtained hits were subjected to molecular properties and PAINS filter. The homology modelling and molecular dynamics (MD) were performed to prepare selected AChE protein model (PDB id 4EY7) for advanced studies. The virtual screening and precision docking led to the identification of five compounds. The ADMET property prediction and free energy calculations were carried out to obtain three final compounds. The Alanine scanning and MD study of the compounds viz. ZINC000013719534, ZINC000035551243 and ZINC000035596918 produced stable complexes of the ligands. The identified virtual leads have the potential for better AChE inhibition. Highlights Pharmacophore mapping of donepezil was developed from PDB id 4EY7. Pharmacophore-based screening yielded 601 compounds with RMSD < 0.5 Å. PAINS and Drug likeliness filtration resulted in 199 compounds for further virtual screening and precision docking studies. Free binding energy and ADMET studies provided three active compounds. The molecular dynamics study indicated that the compounds ZINC000013719534, ZINC000035551243 and ZINC000035596918 formed stable interactions with the protein. © 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group.